Przedmiotowy i podmiotowy zakres obowiązku rolniczego użytkowania gruntów: [A subjective and objective scope of a duty of agricultural exploitation of land] (Studia Prawnicze / The Legal Studies, 2023)
When putting the freeholder under an obligation to exploit the land (Article 16 of the Act of 26 X 1971) the legislator leaves it to the organs of administration to assess how and to what degree this duty is fulfilled. A negative assessment is tantamount to the application of administrative sanctions against the peasant (Article 21).Having assumed that agricultural exploitation of land embraces not only its cultivation but also productive utilization, the universal criteria of assessment should be worked out, which would simultaneously set up the confines of legal-administrative liability of free-holders. Foreign legislation provides numerous solutions to this problem: through either establishing the range of peasant’s duties at the level of the average extensive cultivation typical of a locality (Jugoslavia), or detailed ennumeration of all duties relating to both the cultivation of land and its productive exploitation (The German Democratic Republic and the Soviet Union), finally through the transfer of competence, pertaining to imposing obigations and the specification of its range, to the agricultural producers’ managerial cooperations (France). With a view to specifying a subjective scope of the duty, as provided by the Article 16, it is necessary to avail of a comprehensive legislation which would counteract the productive inactivity of individual farms. The regulations, which provide the premisses to account a farm to be -neglected, economically deteriorated or abandoned, have been recognized by jurisprudence as independent legal grounds to construe the duty of agricultural exploitation of land. Moreover, they are in direct connection with a solution applied in the Article 16. Therefore it can be assumed that adequately modified criteria to account a farm to be neglected, when availing of a notion of productive minimum, will provide the range of legal-administrative libility of the freeholder or lessee.The execution of administrative measures against a farmer who has not fulfilled the duty of agricultural exploitation of land, is a condition to evidence whether the reasons of negligence are justifiable or not. In the majority of caxses it is possible to take appropriate decision in this respect availing of the objective criterion of conscientiousness, that has already been adopted by civil law to determine a guilt on a premises of responsibility. However, due mention should be made of the statutory duty provided for by the Article 16, which does not require personal activities of a subject under obligation. Therefore the criterion of conscientiousness refers to the assessment of the latter as an organizer rather than executor. Moreover, such objective reasons as sickness or old age are sufficient to justify an unfulfilled duty.The duty provided for by the Article 16 was imposed on freeholders, as well as dependent and independent tenant farmers. Such specification of addressees excludes state organizational units. The system and functional interpretation of law favours further limitation of addressees to individual farmers and legal persons, other than the units of socialized economy. The construction of liability for neglecting one’s duty and the nature of the sanctions applicable are the case against recognizing freeholders as a party to action taken in accordance with the Article 21, side by side with tenant farmers. Therefore it can be assumed that the lease of lands exempts the freeholder from an obligation of their agricultural exploitation. On the other hand the negligence by the tenant can affect the freeholder if the condition of a farm requires an obligatory repurchase.